Dinamika hubungan kekuasaan pusat dan daerah - Sunarso Sunarso (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
In 2001 President Wahid made a significant change in the administrative systemfrom a highly centralised to a decentralised system. After the downfall of Soeharto,governors, regents and mayors, who had felt the unfair distribution of resources, started to claim a greater share of their resources. In the implementation of local autonomy the relationship between the central and the localgouemments and the respective functions of each administrative level became crucial. Regional autonomy aimed at changing the balance between the central bureaucracy and the Iocal btaeaucracy, and between upper leuel bureaucracy and lozaer level bureaucracy. The need to change the concentration of power and resouces in the hands of power holders and, informally, also in hands of its cronies, was a logical consequence of the struggle to eliminate cronyism and collusion:  According to Law Na 22 of 1999 on Local Government, districts had full autonomy.  This meant that the provincial governor continued to act as the representative of the central government in the province, but that the head of a district could no longer be regarded as a representative ofcentral government The governor had a dual role as head of the autonomous region, the governor did not have power over the regent. As the central government representative, however, the governor clearly had the power of the centre to supervise and to facilitate the district and city governments.